Pengembangan Website untuk Menampilkan Harga Koin Kripto dengan Antarmuka Pemrograman Aplikasi - Rizky Parlika; Achmad Yuneda Alfajr; Alif Ernanda Putra; Ahmad Dendy Prasongko Putra (Maranatha University Press, 2022)
Cryptocurrency is one of the investment instruments and trading assets chosen by old and new traders today. Lots of people claim that the information from the platforms they use is just numbers or trivial information. However, many ordinary people who really need it are still confused about this information. In this study, an application programming interface was developed to help new traders using the instrument easier.